The Correlation between Students' Motivation and Students' Reading Ability - Afi Dhatul Azhari (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2020)
Abstract: The aim of this study is to find out the correlation between students’ reading motivation and students’ reading ability. To know whether there is a correlation between the two variables, researcher uses correlational research. The population of this research was the students in the third semester of English Department at University of Islam Malang in academic year 2019/2020.The respondents of this research were 58 students from the total two classes. The instruments that used by the researcher were questionnaire and taking the reading score from the lecturer. The questionnaire was used to measure the students’ motivation in reading and score from the lecturer was used to measure the students’ reading ability. In analyzing the data, researcher uses SPSS 17.0. The result showed that the mean of students’reading  motivation is 61.47 with standard deviation 11.503. Moreover, the mean of reading ability is 60.69 with standard deviation 16.298. Also, in this study, the significant value was found 0.438.  It means that the significant value was more than 0.05. In other word, the alternative hypothesis (Ha) is rejected, and the null hypothesis (Ho) is accepted. So, it can be concluded that there is no correlation between students’ motivation and students’ reading ability.Based on the finding of the study, it addressed to lecturers to give the motivation to their students. It can help students to build their spirit in achieving something they want. Also, students must have motivation in learning. Motivation can spur them to doing effort continuously so that can reach what they want. Then, having more innovation can be conducted deeply in other research by the future researchers.  Keywords: Students’ motivation, reading ability.